(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
This study aims to determine: 1) The effect of perceived usefulness on customer loyalty. 2) The effect of perceived convenience on customer loyalty. 3) The effect of perceived trust on customer loyalty. 4) The effect of perceived usefulness on customer loyalty which is mediated by customer satisfaction. 5) The effect of perceived convenience on customer loyalty mediated by customer satisfaction. 6) The effect of perceived trust on customer loyalty mediated by customer satisfaction. The sampling technique uses nonprobability sampling. Data was obtained through distributing online questionnaires to active BCA Mobile users and using its service features at least twice in the last three months, for data analysis using Partial Least Square (PLS) with SmartPLS 4.1.0.1 software. The results of this study show that: 1) Perceived usefulness has no effect on customer loyalty. 2) Perceived convenience has no effect on customer loyalty. 3) Perceived trust has an effect on customer loyalty. 4) Customer satisfaction does not mediate perceived usefulness on customer loyalty. 5) Customer satisfaction does not mediate perceived convenience on customer loyalty. 6) Customer satisfaction mediates perceived trust on customer loyalty.